Fillers in Finals of National School Debating Championships - Rahmawati, Yuni; Farida, Alief Noor (Journal of English Language and Education, 2025)
Fillers, such as “uh” and “uhm,” played a crucial role in spontaneous spoken communication. Despite their importance, research on fillers in debate competitions remained limited, with most studies focusing on classroom contexts. This study addressed this gap by examining the types and functions of fillers used in National School Debating Championships (NSDC) 2023 and 2024, highlighting their pedagogical implications. Using a descriptive qualitative case study approach, it analyzed utterances with fillers from debate finals. The findings revealed that lexicalized fillers, such as repetitive phrases, were used more frequently than unlexicalized fillers. Additionally, fillers served five functions: hesitation, mitigation, time-creating, empathizing, and editing-term devices. These insights underscored the importance of incorporating fillers into English teaching and learning to enhance fluency and confidence. By understanding how to use fillers strategically, students could improve their speaking skills, particularly in high-pressure environments like debates.